The Relevance of Confucian Values to Leadership Communication - Joyce Cheah, Lynn-Sze; Norhafezah Yusof,; Mohd Khairie Ahmad, (Universiti Kebangsaan Malaysian, 2014)
Research on leadership communication is still an active area of inquiry as can be seen from the growing number of studies employing different perspectives to enhance the contributions of the field in its own right. From the intercultural communication perspective, every culture provides a particular view of leadership communication because each culture has tended to look at certain cultural conceptual artifacts differently. For example, in Asia, the studies on leadership communication tended to focus on Japanese and Korean and there are only a few studies which have used other cultural notions like the ones carried out in Malaysia. Among the challenges faced by the leaders in Malaysia are the ways to remain relevant in light of rapid changes in the country. The priority is, therefore, to be able sustain the impressive achievements made thus far in the rather challenging context of a multi-racial and multi-religious society, especially the need to understand the cultural thinking of the Chinese community after the recent General Election (GE13). This article discusses the Chinese and Western leadership cultures and the roles of Confucian values in leadership communication in East Asia. On the basis of insights gained, a model has been proposed to guide the development of subsequent leadership communication studies, particularly that which involves the Chinese community in Malaysia.